ANALISIS PENGARUH FIRM SIZE, AUDITOR, INCOME, OPINION, DAN LEVERAGE TERHADAP AUDIT DELAY YANG TERDAFTAR DI BURSA EFEK INDONESIA - Jenifer, Jenifer; Hendi, Hendi (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
Public Bookkeeping Companies in good standing are judged to be able to conduct reviews more effectively and to have larger schedules to handle reviews as needed, allowing clients to obtain data from budget summaries and pursue financial options more quickly. The purpose of this research is to find out whether firm size, auditor size, income, and opinion have a significant effect on audit delay. This study was designed based on causality research, which is a research implementation with an emphasis on the influence between one variable and another. The research method used in this thesis is a quantitative approach. The results of the study show that income has a significant positive effect on audit delay. Other variables, namely firm size, auditor size, opinion, and leverage, have no significant effect on audit delay.